The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.stam.2006.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bacteria and viruses from waters using layered double hydroxide nanocomposites

Abstract: We have identified synthetic layered double hydroxides (LDH) nanocomposites as an effective group of material for removing bacteria and viruses from water. In this study, LDH nanocomposites were synthesized and tested for removing biological contaminants. LDH was used to remove MS2 and fX174 (indicator viruses), and Escherichia coli (an indicator bacterium) from synthetic groundwater and to remove mixed communities of heterotrophic bacteria from raw river water. Our results indicate that LDH composed of magnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 16 publications
2
46
0
1
Order By: Relevance
“…strain ADP was dramatically enhanced in the presence of Mg 2 Al(OH) 6 NO 3 ·nH 2 O hydrotalcite like compound (Layered Double Hydroxides or LDH) although AT was not sorbed on this inorganic matrix. A few other papers have reported that microorganisms can strongly interact with LDH [7,25], the purpose of all these experiments being to set up efficient anti-microbial processes or wastewaters treatments. LDH is a class of ionic lamellar minerals with positively charged hydroxylated layers of divalent and trivalent metallic cations ([M II 1−x M III x (OH) 2 ] x+ ) and exchangeable hydrated gallery anions ([X q− x/q ·nH 2 O]) [26].…”
Section: Introductionmentioning
confidence: 99%
“…strain ADP was dramatically enhanced in the presence of Mg 2 Al(OH) 6 NO 3 ·nH 2 O hydrotalcite like compound (Layered Double Hydroxides or LDH) although AT was not sorbed on this inorganic matrix. A few other papers have reported that microorganisms can strongly interact with LDH [7,25], the purpose of all these experiments being to set up efficient anti-microbial processes or wastewaters treatments. LDH is a class of ionic lamellar minerals with positively charged hydroxylated layers of divalent and trivalent metallic cations ([M II 1−x M III x (OH) 2 ] x+ ) and exchangeable hydrated gallery anions ([X q− x/q ·nH 2 O]) [26].…”
Section: Introductionmentioning
confidence: 99%
“…550 °C) to yield low crystalline mixed oxides and then reconstructed by treatment with aqueous solutions containing anionic species [16,17]. In view of all this information, our work has focused on obtaining nanostructured ensembles able to combine the properties of the biocompatible matrix of the anionic clay and the specific induced characteristics of the nanosized metals into one single material.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to serving as sorbent for organic and inorganic contaminants, current technology has used CNTs as nanofilters to reduce particle concentrations in waste water (Srivastava et al, 2004;Jin et al, 2007;Tahaikt et al, 2007). Similar to sorbents, specific selectivity on CNTs filters can be manipulated through the attachment of different functionalities at the pore entrances (Fornasiero et al, 2008).…”
Section: Carbon Nanotubes In Waste Water Treatmentmentioning
confidence: 99%